2014
DOI: 10.1007/978-3-0348-0837-8_7
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Inflammation in Prostate Cancer

Abstract: In the United States and in "Westernized" countries, the prevalence of both prostate cancer and prostate inflammation is very high, indicating that the two pathologies could be causally related. Indeed, chronic inflammation is now regarded as an "enabling" characteristic of human cancer. Prostate cancer incidence is thought to be mediated in part by genetics, but also by environmental exposures, including the same exposures that may contribute to the development of prostatic inflammation. As our understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 178 publications
(197 reference statements)
1
82
0
1
Order By: Relevance
“…Induction and progression of cancers depend on the immune system whose cells have the potential to be both anti- or pro-tumorigenic, which depends on cellular phenotypes and the tumor microenvironment [18]. In prostate microenvironment, chronic inflammation is involved in PCA carcinogenesis [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Induction and progression of cancers depend on the immune system whose cells have the potential to be both anti- or pro-tumorigenic, which depends on cellular phenotypes and the tumor microenvironment [18]. In prostate microenvironment, chronic inflammation is involved in PCA carcinogenesis [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Other issues are also of importance: it is unlikely that infectious agents are evenly distributed in the (diseased) prostate; thus, the investigation of only one tissue sample per patient might not be sufficient to detect microorganisms. Indeed, Sfanos et al [4,17] showed that detection rates were highly dependent on the number of samples taken per patient: When only one biopsy needle core was investigated, 50% of patients were PCR positive for 16S rRNA. However, when investigating three cores per patient the detection rate increased to 87%.…”
Section: Methodologiesmentioning
confidence: 99%
“…Contamination can potentially be introduced during sample collection or after resection if samples are stored under non-sterile conditions. Indeed, it is challenging to collect human prostate tissue samples under completely sterile conditions [17,18]. Biopsy samples are collected with a biopsy needle that needs to traverse a typically 'contaminated' surface, the rectum.…”
Section: General Considerationsmentioning
confidence: 99%
“…However, the accurate etiology and pathogenesis remain inconsistent. Recently, a number of studies suggested that inflammation and genetic factors may play an important role in the etiology of prostate cancer (8)(9)(10)(11)(12)(13)(14). The prostaglandin-endoperoxide synthase 2 gene that encodes the cyclooxygenase-2 enzyme has been verified to play an important role in the development of prostate cancer in numerous studies (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%